PENGARUH SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. POST ENERGY INDONESIA - Dedi Mulyadi (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
This study aims to determine the effect of occupational safety and health management systems (SMK3) and the work environment on employee work productivity. This study uses quantitative methods with data collection through observation, questionnaires, and interviews. The data analysis technique of this research is using path analysis. The results of this study prove that there is a relationship or correlation between the occupational safety and health management system (X1) and the work environment (X2). Furthermore, there is a partial influence of the occupational safety and health management system and the work environment on employee work productivity. Simultaneously, there is a significant influence between the occupational safety and health management system and the work environment on employee work productivity.